Surgical treatment of massive pulmonary thromboembolism due to renal cell carcinoma - AK, KORAY; ÖZTÜRK, FATİH; ARSAN, SİNAN (My University, 2022)
While renal cell carcinomas frequently invade the renal vein and inferior vena cava, the right atrial extension or formation of bilateral pulmonary massive embolism is quite unusual. A 65-year-old male patient underwent bilateral pulmonary tumor endarterectomy and total thrombectomy of the inferior vena cava combined with left nephrectomy under total circulatory arrest with antegrade cerebral perfusion. Both mediastinal and abdominal approaches facilitated the complete removal of the caval thrombus under the guidance of transesophageal echocardiography. The patient is still under follow-up for six months without metastasis. In conclusion, pulmonary thromboembolism due to renal cell carcinoma is rare, surgical treatment is possible.

Renal hücreli karsinom, renal veni ve inferior vena kavayı sıklıkla invaze ederken, sağ atriyuma ilerlemesi veya iki taraflı pulmoner masif emboliye neden olması oldukça nadirdir. Altmış beş yaşında erkek hastaya total dolaşım arresti altında ve antegrad serebral perfüzyon kullanılarak eş zamanlı sol nefrektomi ile birlikte iki taraflı pulmoner tümör endarterektomisi ve inferior vena kavanın total trombektomisi yapıldı. Transözefageal ekokardiyografinin kılavuzluğu altında her iki mediastinal ve abdominal yaklaşım, inferior vena kavadaki trombüsün tamamen çıkarılmasını kolaylaştırdı. Hasta altı aydır halen metastaz olmaksızın takip edilmektedir. Sonuç olarak, renal hücreli karsinoma bağlı pulmoner tromboembolizm nadir görülmekle birlikte, cerrahi tedavisi mümkündür.
Renal hücreli karsinoma bağlı masif pulmoner tromboembolinin cerrahi tedavisi
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Inferior vena cava; pulmonary embolism; renal cell carcinoma; Inferior vena cava; pulmonary embolism; renal cell carcinoma; İnferior vena kava; pulmoner emboli; renal hücreli karsinom